The mechanism of coupling and coordination between the rule of law and sustainable development from a system theory perspective: evidence from China - Zhou, Qiancheng; Zhang, Liwei; Nian, Chenxi (Frontiers in Public Health, 2025)
The rule of law and sustainable development are two core elements in addressing the challenges of national reform and transformation. To further clarify the roles and relationship between these two aspects, this paper innovatively proposes a coupling coordination mechanism for the rule of law and sustainable development. Using evidence from China, this study first constructs an indicator system for both elements from a systems theory perspective. Through empirical research, the entropy method and coupling coordination degree model are employed to measure the development levels and coupling coordination effects of the rule of law and sustainable development. Additionally, the grey relational model is utilized to quantify the factors influencing the interaction between the two during the coupling process, and practical pathways for promoting their coordinated development are proposed. The findings reveal a significant upward trend in the coupling coordination relationship between the rule of law and sustainable development over the past decade, evolving from severe imbalance to high-quality coordination. Notably, the rule of law environment and social rule of law have a significant impact on sustainable development, while economic, ecological, and political sustainability notably influence the rule of law. This study not only elucidates the coupling coordination relationship and mutual influences between the rule of law and sustainable development but also provides theoretical insights and practical guidance for advancing national modernization and addressing development challenges in other countries.